A method for preparing a rare earth modified AlTiVCrMo high-entropy alloy coating for a fuel cell bipolar plate
Patent Information
- Application Number
- CN202610914170.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-27
AI Technical Summary
其虽然表现出较好性能,但改性氧化石墨烯制备工艺复杂(需对苯二胺接枝、碳纳米管杂化、多步离心洗涤),涉及高温长时反应(80-120°C反应12-24h)和有机溶剂(NMP)使用,工业化放大成本高、批次一致性控制难度大
1、纳米级纯Ti过渡层与304不锈钢、上层高熵合金均具备良好化学相容性,形成冶金结合;Ti-AlTiVCrMo梯度过渡层实现成分连续渐变,缓解基体与功能层之间热膨胀系数、力学性能差异,消除界面应力集中,有效避免涂层服役过程中剥落,涂层结合强度可达30N以上。
Smart Images

Figure CN122979840A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of surface treatment technology, specifically to a method for preparing a rare earth-modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates. Background Technology
[0002] Metal bipolar plates are the core structural and functional components in fuel cell stacks, and they have a decisive impact on the overall performance, lifespan, and economy of fuel cells. Their material properties directly affect the energy conversion efficiency and service life of fuel cell systems.
[0003] Metal bipolar plates face severe corrosion and passivation problems under typical fuel cell service environments (acidic electrolyte conditions pH 3-5, operating temperature 60-95℃). The metal substrate is prone to forming an unstable oxide film in acidic and high-potential environments. This oxide film layer leads to a significant increase in interfacial contact resistance, thereby reducing the stack output power.
[0004] Surface protection and interface control of metal bipolar plates are key technologies for improving the reliability and durability of fuel cells. Current selection of surface coating materials for metal bipolar plates focuses on ceramics and some alloys, and various technical approaches have been explored, but all have certain limitations. For example, patent document CN121759902A discloses a method for preparing a metal bipolar plate coating, which adopts a gradient multilayer structure. First, a Ti layer is deposited using DC magnetron sputtering. On the Ti layer, a TiAlN ceramic layer is deposited using high-power pulsed magnetron sputtering. On the TiAlN ceramic layer, a noble metal (Au) layer is deposited using radio frequency sputtering (RF). Although it exhibits excellent conductivity and corrosion resistance, the cost of noble metal materials is too high. This constitutes a significant economic obstacle for large-scale automotive fuel cell applications. Furthermore, the Au layer is the outermost layer; if pinholes or cracks appear in the Au layer, the exposed base metal (TiAlN) will form micro-cells that accelerate corrosion.
[0005] In addition, some studies have focused on optimizing coating composition. For example, patent document CN121873653A discloses a metal surface anti-corrosion coating and its preparation method and application. A composite coating is constructed using an alloy layer and a wear-resistant layer. The alloy layer (Zn-Al-Mo) is directly attached to the metal substrate surface as the bottom protective layer, while the wear-resistant layer (polyurethane-based: 6.5-9.7% modified graphene oxide, 4.7-7.9% flake zirconium phosphate powder, 68.2-86.4% polyurethane resin, 0.3-0.9% rare earth oxide nanoparticles, 4.3-6.4% filler, 2.6-4.3% dispersant) is attached above the alloy layer as the outer functional layer. Although it exhibits good performance, the preparation process of modified graphene oxide is complex (requiring grafting of p-phenylenediamine, carbon nanotube hybridization, and multi-step centrifugal washing), involving high-temperature long-time reactions (80-120°C for 12-24 hours) and the use of organic solvents (NMP). Industrial scale-up is costly and batch consistency control is difficult. Meanwhile, both magnetron sputtering and electrostatic spraying processes have high equipment investment and operating costs, and are subject to constraints on workpiece size and shape, making them unsuitable for on-site construction of large or complex structural components.
[0006] Therefore, in view of the above-mentioned defects of the existing technology, it is urgent to develop a metal bipolar plate coating that has both excellent conductivity and corrosion resistance, and to adapt its preparation process to the needs of large-scale industrial production, under the premise of controllable cost. Summary of the Invention
[0007] To address the aforementioned issues, this invention provides a method for preparing a rare-earth modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates. This method employs a multi-layer gradient structure consisting of a pure Ti underlayer, a Ti-AlTiVCrMo gradient transition layer, and a rare-earth modified high-entropy alloy functional layer. Combined with CeO2 and Y2O3 rare-earth oxide co-sputtering modification, the coating's corrosion resistance, conductivity, and film-substrate bonding strength are synergistically optimized under a single magnetron sputtering process. The process parameters are controllable, no organic solvents are used, making it suitable for large-scale industrial production and effectively extending the service life of fuel cell metal bipolar plates.
[0008] To achieve the above objectives, the technical solution of the present invention is as follows: A method for preparing a rare earth-modified AlTiVCrMo high-entropy alloy coating for a fuel cell bipolar plate, comprising: using a fuel cell bipolar plate as a substrate and pre-treating it by cleaning; depositing a pure Ti transition layer on the surface of the pre-treated substrate; depositing a Ti-AlTiVCrMo gradient transition layer on the surface of the pure Ti transition layer; depositing an AlTiVCrMo-(CeO2 / Y2O3) rare earth-modified composite coating on the surface of the Ti-AlTiVCrMo gradient transition layer; and completing the preparation of the rare earth-modified AlTiVCrMo high-entropy alloy coating on the surface of the fuel cell bipolar plate.
[0009] Furthermore, the fuel cell bipolar plates are made of polished 304 stainless steel; the cleaning pretreatment includes ultrasonic cleaning with alcohol and ultrasonic cleaning with deionized water.
[0010] Furthermore, before depositing a pure Ti transition layer on the pretreated substrate surface, the pretreated substrate is fixed onto the substrate of the vacuum coating equipment and placed into the vacuum chamber of the vacuum coating equipment. The vacuum chamber is evacuated to a minimum of 3 Pa. Argon gas is introduced and the substrate bias power supply is turned on to perform bias cleaning on the substrate.
[0011] Furthermore, after completing the bias cleaning, a two-stage vacuum evacuation is performed on the vacuum chamber until the base vacuum level of the vacuum chamber reaches 3×10⁻⁶. -3 Below Pa, open the gas path and set the argon flow rate to 20-30 sccm to stabilize the working pressure of the cavity at 0.3-0.5 Pa; wait for the molecular pump speed to reach 26000-28000 r / min, and heat for 0.5-1 h to raise the temperature of the vacuum chamber to 140-160℃; then turn on the DC power supply of the pure Ti target and perform pre-sputtering cleaning on the target surface for 10-30 min.
[0012] Further, a pure Ti transition layer is deposited on the pretreated substrate surface, including: sequentially opening the target baffle and substrate baffle of the vacuum coating equipment and starting the substrate rotation to begin the deposition of the pure Ti transition layer, with the sputtering power set to 70-130W, the substrate bias voltage set to 70-130V, and the deposition time to 10-30min.
[0013] Furthermore, the pure Ti target material is a 99.9% pure Ti target material, and the thickness of the deposited pure Ti transition layer is 50-120 nm.
[0014] Further, a Ti-AlTiVCrMo gradient transition layer is deposited on the surface of the pure Ti transition layer, including: maintaining the vacuum chamber temperature of the vacuum coating equipment at 140-160℃, setting the argon flow rate to 20-30 sccm, and stabilizing the vacuum chamber pressure at 0.3-0.5 Pa; then turning on the pulse power supply of the AlTiVCrMo alloy target, adjusting the power of the two power supplies in real time, increasing the power of the AlTiVCrMo alloy target from 0W to 25-75W, and decreasing the power of the pure Ti target from 70-130W to 0W, forming a gradient structure transition layer, with a substrate bias voltage of -70-130V and a deposition time of 10-30min.
[0015] Furthermore, the atomic ratio of the AlTiVCrMo alloy target is Al:Ti:V:Cr:Mo = 14.43:24.21:19.63:17.20:24.35.
[0016] Furthermore, an AlTiVCrMo-(CeO2 / Y2O3) rare earth modified composite coating is deposited on the surface of the Ti-AlTiVCrMo gradient transition layer, including: maintaining the vacuum chamber temperature of the vacuum coating equipment at 140-160℃, setting the argon flow rate at 20-30 sccm, and stabilizing the vacuum chamber pressure at 0.3-0.5 Pa; keeping the pulse power supply of the AlTiVCrMo alloy target on, turning off the DC power supply of the pure Ti target, and starting the RF power supply of the (CeO2 / Y2O3) target; setting the sputtering power of the AlTiVCrMo target to 25-75W, the sputtering power of the (CeO2 / Y2O3) target to 10-50W, the substrate bias voltage to 70-130V, and the deposition time to 1-3h.
[0017] Furthermore, the rare earth oxides are CeO2 or Y2O3 with a purity of 99.9%; and the amount of rare earth oxides added is controlled by a radio frequency power supply.
[0018] The beneficial effects of this invention are: 1. The nano-grade pure Ti transition layer has good chemical compatibility with 304 stainless steel and the upper high-entropy alloy, forming a metallurgical bond; the Ti-AlTiVCrMo gradient transition layer achieves a continuous and gradual change in composition, alleviates the difference in thermal expansion coefficient and mechanical properties between the substrate and the functional layer, eliminates interfacial stress concentration, effectively avoids peeling off the coating during service, and the coating bonding strength can reach more than 30N.
[0019] 2. Rare earth oxides can refine coating grains, seal micropores and corrosion channels, and form a dense passivation film in acidic and high-temperature environments to block the penetration of corrosive media; CeO2 modification can change the coating from hydrophilic to hydrophobic, and the corrosion current density is reduced by 1 to 2 orders of magnitude compared with the unmodified coating; Y2O3 can play a role in grain boundary pinning and interface purification, maintaining high conductivity and strong adhesion of the coating while ensuring corrosion resistance, and solving the problem of performance imbalance of single high-entropy alloy coatings.
[0020] 3. The entire process uses only a single magnetron sputtering process, eliminating the need for organic solvents, complex precursor preparation, and multi-equipment operation; the process parameters have a wide range and are easy to control, resulting in good batch product consistency. It can be adapted to various types of fuel cell metal bipolar plates, such as flat-plate and flow-channel types, and is also suitable for mass production of large components.
[0021] 4. In a simulated acidic fuel cell environment of 75℃, 0.5mol / LH2SO4 + 1mg / LHF, the coating exhibits a corrosion current density of less than 0.5μA / cm², low contact resistance, and long-term resistance to acidic media corrosion, significantly improving the operational stability and service life of the metal bipolar plate. Attached Figure Description
[0022] Figure 1This is a process flow diagram of the method for preparing rare earth modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to the present invention. Figure 2 This is a schematic diagram of the prepared AlTiVCrMo high-entropy alloy coating structure; Figure 3 Fitting results of electrochemical corrosion test data of coatings under different process parameters; Figure 4 A schematic diagram of the corrosion morphology of CeO2-modified AlTiVCrMo high-entropy alloy coating after potentiodynamic polarization; Figure 5 A schematic diagram of the corrosion morphology of the Y2O3-modified AlTiVCrMo high-entropy alloy coating after potentiodynamic polarization. Detailed Implementation
[0023] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] The substrate of this invention is a polished 304 stainless steel plate, which serves as a simulated bipolar plate sample for a fuel cell. The preparation equipment is a vacuum coating system, specifically a JCP500 high-vacuum magnetron sputtering system from Beijing Taicono Technology Co., Ltd. Target parameters include: pure Ti target (99.9% purity), AlTiVCrMo high-entropy alloy target (atomic ratio of Al:Ti:V:Cr:Mo = 14.43:24.21:19.63:17.20:24.35), and rare earth oxide targets (CeO2 target and Y2O3 target, both with 99.9% purity). The following examples illustrate this further: Reference steps for the preparation of rare earth modified AlTiVCrMo high-entropy alloy coating Figure 1 As shown, the rare earth-modified AlTiVCrMo high-entropy alloy coating structure reference Figure 2 As shown; the following detailed description is provided through specific implementation methods: Example 1: Using CeO2 as a rare earth modifier, a 40mm × 40mm × 2mm polished 304 stainless steel sample was ultrasonically cleaned for 30 minutes with 99% ethanol at room temperature, followed by two ultrasonic cleanings with deionized water (10 minutes each). The sample was then removed and air-dried in a clean environment. The sample was fixed onto a substrate in a magnetron sputtering device and placed in a vacuum chamber. A mechanical pump was started to evacuate the vacuum to below 3 Pa (e.g., 2.5 Pa), argon gas was introduced, and the substrate bias power supply was turned on to complete the substrate bias cleaning.
[0025] After cleaning, turn off the argon gas and start the molecular pump for secondary vacuuming until the chamber's base vacuum reaches 3 × 10⁻⁶. -3 Pa below (e.g., 2.8 × 10) -3 Pa); the molecular pump speed was 27000 r / min, the chamber was heated for 0.5 h, and the temperature rose to 150℃; the argon flow rate was adjusted to 25 sccm, and the working pressure of the chamber was stabilized at 0.5 Pa; the pure Ti target DC power supply was turned on, and pre-sputter cleaning was performed for 20 min.
[0026] After pre-sputtering cleaning, the target baffle and substrate baffle are opened, and the substrate rotation is started; the Ti target sputtering power is 70W, the substrate negative bias voltage is -75V, and a pure Ti transition layer is deposited for 30min; the thickness of the obtained pure Ti transition layer is 50nm.
[0027] After completing the deposition of the pure Ti transition layer, the chamber temperature was kept at 150℃, the argon gas pressure at 25 sccm, the chamber working pressure at 0.5 Pa, and the substrate bias at -75V. The AlTiVCrMo alloy target power was turned on and the power was adjusted in a gradient: the AlTiVCrMo target power was increased from 0W to 50W, and the pure Ti target power was decreased from 70W to 0W. The Ti-AlTiVCrMo gradient transition layer was deposited for 30 min.
[0028] After completing the Ti-AlTiVCrMo gradient transition layer deposition, the pure Ti target power supply was turned off, and the AlTiVCrMo target power was maintained at 50W. The CeO2 target RF power supply was turned on, with a sputtering power of 30W, a substrate negative bias of -75V, and a deposition time of 2 hours.
[0029] After completing the deposition of each layer, all power and gas lines are turned off. The chamber is cooled to below 50°C under vacuum. The sample is then removed to obtain a rare earth modified AlTiVCrMo high-entropy alloy anti-corrosion and conductive coating for fuel cell bipolar plates.
[0030] Example 2: Using Y2O3 as a rare earth modifier, a 40mm × 40mm × 2mm polished 304 stainless steel sample was ultrasonically cleaned for 30 minutes with 99% ethanol at room temperature, followed by two ultrasonic cleanings with deionized water (10 minutes each). The sample was then removed and air-dried in a clean environment. The sample was fixed onto a substrate in a magnetron sputtering device and placed in a vacuum chamber. A mechanical pump was started to evacuate the vacuum to below 3 Pa (e.g., 2.5 Pa), argon gas was introduced, and the substrate bias power supply was turned on to complete the substrate bias cleaning.
[0031] After cleaning, turn off the argon gas and start the molecular pump for secondary vacuuming until the chamber's base vacuum reaches 3 × 10⁻⁶. -3 Pa below (e.g., 2.8 × 10) -3Pa); the molecular pump speed was 27000 r / min, the chamber was heated for 0.5 h, and the temperature rose to 150℃; the argon flow rate was adjusted to 25 sccm, and the working pressure of the chamber was stabilized at 0.5 Pa; the pure Ti target DC power supply was turned on, and pre-sputter cleaning was performed for 20 min.
[0032] After pre-sputtering cleaning, the target baffle and substrate baffle are opened, and the substrate rotation is started; the Ti target sputtering power is 70W, the substrate negative bias voltage is -75V, and a pure Ti transition layer is deposited for 30min; the thickness of the obtained pure Ti transition layer is 50nm.
[0033] After completing the deposition of the pure Ti transition layer, the chamber temperature was kept at 150℃, the argon gas pressure at 25 sccm, the chamber working pressure at 0.5 Pa, and the substrate bias at -75V. The AlTiVCrMo alloy target power was turned on and the power was adjusted in a gradient: the AlTiVCrMo target power was increased from 0W to 50W, and the pure Ti target power was decreased from 70W to 0W. The Ti-AlTiVCrMo gradient transition layer was deposited for 30 min.
[0034] After completing the Ti-AlTiVCrMo gradient transition layer deposition, the pure Ti target power supply was turned off, and the AlTiVCrMo target power was maintained at 50W. The Y2O3 target RF power supply was turned on, with a sputtering power of 40W, a substrate negative bias of -75V, and a deposition time of 2 hours.
[0035] After completing the deposition of each layer, all power and gas lines are turned off. The chamber is cooled to below 50°C under vacuum. The sample is then removed to obtain a rare earth modified AlTiVCrMo high-entropy alloy anti-corrosion and conductive coating for fuel cell bipolar plates.
[0036] The difference between Example 1 and Example 2 lies in the rare earth modifier material. Example 1 uses CeO2 as the modifier, while Example 2 uses Y2O3. Due to the CeO2 doping in Example 1, the hydrophobicity and corrosion resistance of the coating are significantly improved, but its adhesion and conductivity are relatively poor. In Example 2, modification with Y2O3 aims to comprehensively optimize the coating performance. Y2O3 enhances the film-substrate adhesion through mechano-chemical coupling and exerts grain boundary pinning and interface purification effects, achieving synergistic optimization of corrosion resistance, conductivity, and interfacial bonding strength.
[0037] The effects of each process step on interfacial adhesion, conductivity, and corrosion resistance were systematically evaluated through interfacial bonding strength testing, resistivity detection, contact angle measurement, SEM / EDS surface chemical analysis, and electrochemical testing (potential dynamic polarization, AC impedance spectroscopy, EIS, etc.). The results showed that: (1) Coating performance under different magnetron sputtering process parameters: With variations in parameters (deposition power, substrate bias, argon flow rate), the interfacial bonding strength of the coating initially increases and then decreases. Excessively high or low process parameters negatively impact the interfacial bonding strength. Appropriate adjustment of the magnetron sputtering process parameters can enhance the coating-substrate bonding strength. The electrochemical corrosion behavior of AlTiVCrMo coatings under different magnetron sputtering process parameters was investigated using single-factor experiments. These experiments were conducted in a simulated fuel cell bipolar plate environment (0.5 mol / L H₂SO₄ + 1 mg / L HF mixed solution heated in water at 75°C). The results are as follows: Figure 3 As shown, the electrochemical impedance and potentiodynamic polarization curves of the AlTiVCrMoN coating were analyzed by fitting data. With varying parameters, the coating's corrosion resistance also showed a trend of first increasing and then decreasing. Optimizing the magnetron sputtering process parameters and appropriately adjusting them can achieve the lowest self-corrosion current density and thus the best corrosion resistance. The performance of the AlTiVCrMo coating under optimal conditions (target sputtering power 50W, substrate bias voltage -75V, argon flow rate 25sccm) was analyzed. The coating adhesion reached 44.1N, and the corrosion current density reached 1.265×10⁻⁶. -4 Acm -2 .
[0038] (2) Effect of CeO2 modification on coating Effect of CeO2 doping on interfacial bonding: CeO2 doping has a significant nonlinear modulating effect on the film-substrate bonding strength. Low doping (10-20W) reduces the bonding strength, medium doping (about 30W) brings the bonding strength to its peak (about 30N), while excessive doping (40-50W) leads to a decrease in bonding strength. Appropriate Ce promotes grain refinement, densification, and interfacial purification, while excessive CeO2 tends to agglomerate, forming brittle, weakly bonded phases and introducing stress and porosity.
[0039] Changes in conductivity: With increasing CeO2 content, the resistivity of the coating shows an increasing trend (from approximately 1.46 × 10⁻⁶). -3 Ω·cm increased to approximately 1.66 × 10⁻⁶ -3 The reason is that CeO2 is a low conductivity phase, and the aggregation of particles at the grain boundaries disrupts electron connectivity and increases interface scattering.
[0040] Wettability Regulation: CeO2 modification has a significant non-monotonic regulating effect on the wettability of the coating surface. Without CeO2, the static water contact angle of the coating is about 78°, exhibiting hydrophilic characteristics. When the addition amount increases to 10W, the contact angle drops to about 65°, and the hydrophilicity is further enhanced. This is attributed to the increase in surface free energy by the oxygen-containing polar groups introduced by the nanoparticles. With the addition amount continuing to increase to 30W, the contact angle reaches a peak of 91°, realizing the transformation of the coating from hydrophilic to hydrophobic. However, when the addition amount is further increased to 50W%, the contact angle drops back to about 73°, and the hydrophobicity decreases. This is mainly due to the decrease in surface roughness uniformity and the destruction of the orderliness of the micro-nano structure caused by excessive nanoparticle aggregation, thus weakening the wettability regulation effect.
[0041] Electrochemical and corrosion performance: Both EIS and polarization curves indicate the existence of an optimal CeO2 doping range (approximately 30 W), at which the coating exhibits the best barrier and passivation properties (R0). p Reaching approximately 5.772 × 10 3 Ω·cm 2 , dynamic potential i corr Minimum approximately 3.17 × 10 - 5 A·cm -2 Both low doping (10W) and excessive doping (50W) lead to decreased corrosion resistance. The mechanism is that appropriate amounts of CeO2 fill defects, promote a dense passivation layer, and extend the ion diffusion path. Excessive CeO2, due to agglomeration, interface weakening, and increased porosity, actually provides channels for the corrosive agent. The corrosion morphology after potentiodynamic polarization is as follows: Figure 4 As shown, corrosion products exhibit localized zoning. After corrosion, zonal enrichment was observed, with Al, Ti, V, Mo, and S enriched in the layered regions, primarily corresponding to the mixed aggregation of metal sulfates and metal oxides. F and Cr, enriched in another region, tend to contain fluorides or chromium oxyfluoride compounds. This zoning reflects the selective dissolution synergistically induced by H₂SO₄ and HF, differences in localized acidic oxidizing properties, and the deposition patterns of products within cracks and microchannels. Comparing CeO₂ addition power of 30W and 40W, the coating maintained a relatively intact surface, with only a few pits and smooth surfaces, indicating good corrosion resistance at this dosage.
[0042] CeO2 doping transforms the wettability from hydrophilic to hydrophobic, reducing the self-corrosion current density by nearly an order of magnitude compared to the unmodified coating. However, its adhesion and conductivity are relatively poor, failing to achieve comprehensive performance regulation. (3) Effect of Y2O3 modification on coating The effect of Y₂O₃ on interfacial bonding: Y₂O₃ doping has a significant nonlinear modulating effect on the film-substrate bonding strength. Low doping (10-30W) reduces the bonding strength, medium doping (about 40W) brings the bonding strength to a peak (about 45N), while excessive doping (50W) leads to a decrease in bonding strength. Appropriate Y promotes grain refinement, densification, and interfacial purification, while excessive Y₂O₃ tends to agglomerate, forming brittle, weakly bonded phases and introducing stress and porosity.
[0043] Changes in conductivity: As the Y₂O₃ sputtering power increased from 10 W to 40 W, the coating resistivity increased from 1.0200 × 10⁻⁶. -3 The Ω·cm gradually increased to a peak value of 1.0333 × 10⁻⁶. -3 Ω·cm, slightly decreases to 1.0315×10 at 50W. -3 The overall variation was small (approximately 1.3%), indicating that the conductivity remained relatively stable within the measured power range, but a weak resistivity-increasing effect existed in the medium-to-high power region. With the incorporation of Y₂O₃, an insulating phase or interfacial discontinuities (Y₂O₃ particles, oxide enrichment) and more grain boundaries / defects were introduced into the coating, all of which enhanced electron scattering, leading to an increase in resistivity.
[0044] Electrochemical and corrosion performance: Both EIS and polarization curves indicate the existence of an optimal Y₂O₃ doping range (approximately 40 W), at which the coating exhibits the best barrier and passivation properties (R). p Reaching approximately 3.940 × 10 3 Ω·cm 2 , dynamic potential i corr Minimum approximately 4.405×10 - 5 A·cm -2 The corrosion morphology after electrodynamic polarization is as follows: Figure 5 As shown in the SEM images, the 10W sample exhibits large-scale flaky exfoliation areas, the 20W sample shows blocky corrosion product accumulation, the 30W sample mainly shows isolated pitting corrosion, the 40W sample has the smoothest corrosion morphology, and the 50W sample shows fine cracks or fissures along the oxide layer. The mechanism can be summarized as follows: appropriate and uniform rare earth doping forms a dense and well-adhered rare earth oxide / oxynitride passivation film on the surface / grain boundaries, inhibiting grain growth and micropore connectivity, reducing the electrochemical differences between active sites and interfaces, and improving overall corrosion resistance. Insufficient doping leads to incomplete coverage and peeling, while excessive doping causes embrittlement and cracking, thus reducing the protective effect.
[0045] Y2O3 enhances the film-substrate bonding force through mechanochemical coupling and exerts grain boundary pinning and interface purification effects, thereby achieving synergistic optimization of corrosion resistance, conductivity and interface bonding strength.
[0046] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing a rare-earth modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates, characterized in that, include: Using a fuel cell bipolar plate as a substrate, it is pretreated by cleaning; a pure Ti transition layer is deposited on the surface of the pretreated substrate. A Ti-AlTiVCrMo gradient transition layer was deposited on the surface of a pure Ti transition layer; an AlTiVCrMo-(CeO2 / Y2O3) rare earth modified composite coating was deposited on the surface of the Ti-AlTiVCrMo gradient transition layer; thus completing the preparation of a rare earth modified AlTiVCrMo high-entropy alloy coating on the surface of the fuel cell bipolar plate.
2. The method for preparing rare-earth modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to claim 1, characterized in that, The fuel cell bipolar plates are made of polished 304 stainless steel; the cleaning pretreatment includes ultrasonic cleaning with alcohol and ultrasonic cleaning with deionized water.
3. The method for preparing rare earth-modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to claim 1, characterized in that, Before depositing a pure Ti transition layer on the pretreated substrate surface, the pretreated substrate is fixed onto the substrate of the vacuum coating equipment and placed into the vacuum chamber of the vacuum coating equipment. The vacuum chamber is evacuated to a first-stage vacuum level of less than 3 Pa. Argon gas is introduced and the substrate bias power supply is turned on to perform bias cleaning on the substrate.
4. The method for preparing rare earth-modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to claim 3, characterized in that, After completing the bias cleaning, the vacuum chamber is evacuated in two stages until the background vacuum level of the vacuum chamber is 3×10⁻⁶. -3 Below Pa, open the gas path and set the argon flow rate to 20-30 sccm to stabilize the working pressure of the cavity at 0.3-0.5 Pa; wait for the molecular pump speed to reach 26000-28000 r / min, and heat for 0.5-1 h to raise the temperature of the vacuum chamber to 140-160℃; then turn on the DC power supply of the pure Ti target and perform pre-sputtering cleaning on the target surface for 10-30 min.
5. The method for preparing rare earth-modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to claim 4, characterized in that, Depositing a pure Ti transition layer on the pretreated substrate surface includes: sequentially opening the target baffle and substrate baffle of the vacuum coating equipment and starting the substrate rotation to begin the deposition of the pure Ti transition layer. The sputtering power is set to 70-130W, the substrate bias voltage is set to 70-130V, and the deposition time is 10-30min.
6. The method for preparing rare earth-modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to claim 5, characterized in that, The pure Ti target material is a pure Ti target material with a content of 99.9%, and the thickness of the deposited pure Ti transition layer is 50-120 nm.
7. The method for preparing rare-earth modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to claim 5, characterized in that, Depositing a Ti-AlTiVCrMo gradient transition layer on the surface of a pure Ti transition layer includes: maintaining the vacuum chamber temperature of the vacuum coating equipment at 140-160℃, setting the argon flow rate to 20-30 sccm, and stabilizing the vacuum chamber pressure at 0.3-0.5 Pa; then turning on the pulse power supply of the AlTiVCrMo alloy target, adjusting the power of the two power supplies in real time, increasing the power of the AlTiVCrMo alloy target from 0W to 25-75W, and decreasing the power of the pure Ti target from 70-130W to 0W to form a gradient structure transition layer, with a substrate bias voltage of -70-130V and a deposition time of 10-30 min.
8. The method for preparing rare earth-modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to claim 7, characterized in that, The atomic ratio of elements in the AlTiVCrMo alloy target is Al:Ti:V:Cr:Mo = 14.43:24.21:19.63:17.20:24.
35.
9. The method for preparing rare earth-modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to claim 6, characterized in that, Depositing an AlTiVCrMo-(CeO2 / Y2O3) rare earth modified composite coating on the surface of a Ti-AlTiVCrMo gradient transition layer includes: maintaining the vacuum chamber temperature of the vacuum coating equipment at 140-160℃, setting the argon flow rate to 20-30 sccm, and stabilizing the vacuum chamber pressure at 0.3-0.5 Pa; keeping the pulse power supply of the AlTiVCrMo alloy target on, turning off the DC power supply of the pure Ti target, and starting the RF power supply of the (CeO2 / Y2O3) target; setting the sputtering power of the AlTiVCrMo target to 25-75W, the sputtering power of the (CeO2 / Y2O3) target to 10-50W, the substrate bias voltage to 70-130V, and the deposition time to 1-3h.
10. The method for preparing a rare-earth modified AlTiVCrMo high-entropy alloy coating for fuel cell bipolar plates according to claim 9, characterized in that, The rare earth oxides are CeO2 or Y2O3 with a purity of 99.9%; and the amount of rare earth oxides added is controlled by radio frequency power supply.
Citation Information
Patent Citations
Preparation method of metal bipolar plate coating, metal bipolar plate and fuel cell
CN121759902A
Metal surface anti-corrosion coating as well as preparation method and application thereof
CN121873653A